Rancang Bangun Aplikasi Media Pembelajaran Komputer Untuk Siswa Sekolah Dasar Berbasis Web di SDN Gading 1 Surabaya - Setyowati, Della Witdiya; Sunarto, M.J Dewiyani; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: SDN Gading 1 in learning system conducted by face-to-face between the teacher and the students where the teacher in providing the material simply by using the lecture method, yet maximize media that there are good, so that less students understand the material being taught by the teacher. In addition, the calculation of the value of the subjects reported a student computer is still in the form of a manual. The process of calculating the value recap subjects the students into the old computer so that students can not see the value directly. Solutions to help computer learning problems in SDN Gading 1 is the use of computer learning media applications. This application is also equipped with calculation and reporting value for students. This application is made by a method comprising SDLC waterfall model of the stages of identifying problems, analyzing and designing systems, building systems, and system testing. The results showed that the application is successfully assist teachers in providing the materials and see the reporting of students' grades and students can understand the material and see the value directly. In addition, this application is in conformity with the needs of the user. This is evident from the value of 3.5 on a scale questionnaire 1-4 which shows the results of the application is good. Suggestion that the development of these applications there is a matter of duty, UTS, and UAS so that students can work directly through the medium of computer learning. Keyword: Learning Media, Computer Course, Practical Assessment.